Proses Gotong Royong dalam Pasar Budaya Desa Manyarejo 2020 - Wiwit Hermanto (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2021)
Cultural Market 2020 in Manyarejo Village was held on 13-15 November 2020. Such a cultural event was performed through three activities, i.e. identificatifying of cultural potential, packaging of cultural potential and executing the cultural market. This event invited people to participate actively in each step through mutual cooperation. Mutual cooperation in achieving common goals, is closely related to the culture of Manyarejo village community. Mutual cooperation needed a leader who could move and influence the community, such as community leaders or village officials. The community of Manyarejo village had various cultural potentials which were successfully explored in the process of identifying cultural potential. Identification of cultural potential was the first activity of the Cultural Market 2020 of Manyarejo village. The identification, found various cultural potentials which could be presented like arts, culinary, skills, kids’ games, traditional houses, tradition of bersih desa, religious event and traditional medicine. Then, the cultural potentials were packed and presented in the event in the midst of the Covid-19 pandemic. The presented cultural potentials in this event, were divided into several zones. The aims are to make it easier for the visitors to find what they like and also to make it easier in dividing tehe stalls.